Systematization of the self-assessment process of the Bachelor of Pedagogy degree with emphasis on Didactics in the context of the COVID-19 pandemic in Costa Rica (Revista Electrónica Calidad en la Educación Superior, 2024)
The purpose of this writing is to share some actions, strategies and technological resources used in the implementation of the self-evaluation process with a view to the accreditation of the Bachelor's degree in Pedagogy with an emphasis in Didactics (LPED), of the Division of Educology (DE); as well as offering different alternatives to develop self-assessment processes under a remote presence modality in emerging contexts due to the health emergency. The self-assessment report of the LPED culminated in 2020, an atypical year marked by the COVID-19 pandemic.
Keywords: Pedagogy; self-evaluation; educational quality; higher education; pandemic